Zolpidem in Insomnia Management: Considerations and Side Effects Associated with Long-Term Indiscriminate use (London Journal of Medical and Health Research, 2024)
Introduction: Insomnia, characterized by difficulty initiating or maintaining sleep, is a common condition that significantly impacts individuals’ quality of life and well-being. In the context of pharma- cological treatment, zolpidem has emerged as a widely prescribed option for the effective management of sleep disorders. However, while this medication provides immediate relief for insomnia symptoms, growing concerns have been raised regarding its indiscriminate long-term use and potential side effects. Objectives: This article aims to comprehensively explore the effectiveness of zolpidem in treating insomnia, while highlighting critical considerations and adverse effects associated with its prolonged use. By investigating the relationship between insomnia management with zolpidem and the implications of indiscriminate administration, this study seeks to provide a balanced perspective, fostering a deeper understanding of the risks and benefits involved in the long-term use of this medication. Methods: The methodology involved a literature review of articles published on the “Scielo” and “Pubmed” websites from October 2013 to October 2023. The cited publications are presented in Portuguese and English.
Keywords: Insomnia; zolpidem; and side effects.